A construção do escândalo político midiático na Folha de S. Paulo: uma análise dos seis escandâlos envolvendo ministros do primeiro mandato do governo Dilma Rousseff (2011-2014) - Marques, Vitor William [UNESP] (2015)
This dissertation analyzes the construction of mediatic political scandal in the journalistic discourse of Folha de S. Paulo newspaper. The aim to discuss the emergence of the phenomenon and its features based on the concepts arised from the social theory of the scandal, proposed by John B. Thompson, in dialogue with the concept of social fields defined by Pierre Bourdieu. The object of study is related to the six political scandals involving six ministers dismissed in the first term of President Dilma Rousseffs government (2011) : Antonio Palocci (Ministry of Civil House), Alfredo Nascimento (Ministry of Transport), Wagner Rossi (Ministry of Agriculture), Pedro Novais (Ministry of Tourism), Orlando Silva (Ministry of Sports) and Carlos Lupi (Ministry of Labour). The analyze is based on the Depth Hermeneutics methodology proposed by John B. Thompson in the book Ideology and Modern Culture (1990). The study derives from four search categories: Scandal sequencial structure, Source of the revelations, Prevalence of the scandal in the newspaper edition and Construction of the involved's profiles